Antimicrobial Activity of Actinomyctes from the Rhizosphere of Pandanus Plants (Pandanus spp.) - Putri, Tarissa Eka; Yuliana Retnowati; Novri Youla Kandowangko; Abubakar Sidik Katili; Wirnangsi Din Uno (Journal of Tropical Mycorrhiza, 2025)
This quantitative descriptive research aimed to describe the antimicrobial activity and phylogenetic relationships of Actinomycetes from the rhizosphere of pandan (Pandanus spp.). Soil samples were taken from three different villages in Gorontalo Regency, including Bontula Village, Asparaga Sub-district, Lombongo Village, Suwawa Tengah Sub-district, and Moutong Village, Tilongkabila Sub-district, Bone Bolango Regency. Isolation was carried out using SCA media, resulting in six Actinomycetes isolates with different colony morphologies. Antimicrobial activity tests were carried out using the cross-streak method against Escherichia coli, Staphylococcus aureus, Candida albicans, Fusarium oxysporum, and Neocosmospora solani. The results showed that only one isolate, IRzP-at.k, showed significant antimicrobial activity, against Escherichia coli and Staphylococcus aureus with inhibition zones of 13,31 mm and 13,67 mm, respectively. The IRzP-at.k isolate also showed inhibition against Candida albicans and Fusarium oxysporum with inhibition zones of 34,12 mm and 11,25 mm, but did not show inhibition against Neocosmospora solani. Phylogenetic analysis based on 16S rRNA gene sequences identified the isolate as closely related to Streptomyces vinaceusdrappus (97.42% similarity). This research indicated the potential of the IRzP-at.k isolate as a source of new antimicrobial compounds and strengthens the role of the pandan rhizosphere as a habitat rich in Actinomycetes.